Survival and reproduction of Synthesiomyia nudiseta (Diptera, Muscidae) - Krüger, Rodrigo Ferreira; Krolow, Tiago Kütter; Azevedo, Rodrigo R.; Duarte, Juliano Lessa Pinto; Ribeiro, Paulo Bretanha (Iheringia - Serie Zoologia, 2008)
The reproduction and survival of Synthesiomyia nudiseta (Wulp, 1883) were studied between 22 and 28°C, 70% R.H. and 12h photoperiod. The raw data were analyzed based on age-class, sex life table, Weibull distribution and entropy curve (H). The intrinsic rate of increase (rm), finite rate of increase (λ), net reproduction rate (R0) and mean generation time (T) were 0.534, 1.7, 59.439 and 7.65 respectively, suggesting fast population growth in these conditions. That is caused by the high fecundity that was confirmed for this species with mean number of eggs/female of 266 and mean preoviposition period of 10.25 days. The Weibull survival model showed that the survival was not constant throughout the adults life: the mortality rate was more pronounced after the fourth and fifth week because both sexes had H values intermediate to those theoretically expected (0.0-0.5), showing that the survival curve is rectangular (with more impact of mortality on the fourth and fifth week from pupal emergence). The presented results can be considered as base for detailed studies on dynamics and population growth of this species in natural habitats.
Sobrevivência e reprodução de Synthesiomyia nudiseta (Diptera, Muscidae)
Keywords: Diptera; Muscidae; Synthesiomyia Nudiseta